INTEGRATING MORALITY INTO INTELLIGENT MACHINES – CAN ARTIFICIAL INTELLIGENCE MAKE UNSUPERVISED MORAL DECISIONS? (Annual of the Faculty of Philosophy in Skopje, 2024)
With the expansion of artificial intelligence and advanced technologies, theworld in the 21st century is rapidly changing and imposing new living dynamics. Althoughsuch changes affect all age groups, younger generations accept them faster andreact more positively. The new cohorts - Generation Z and Alpha - live in a digital worldthat affect their lifestyle, interpersonal relations, quality of mental health, psychologicalwell-being and everyday challenges. The presence of the so called “Frankenstein effect”in some adults provoked by the fast development of artificial intelligence and robotics,reflects a “humans versus machines” position, viewing artificial intelligence as athreat to humanity. However, the reality is that digital and human world are not inconflict, since many people are already using artificial intelligence tools on daily basis.It is implemented in certain aspects of medicine, education, business, law, agriculture,industry, space technology and in many other fields. With this in mind, the aspect ofmorality pops up as a very important one. A frequently asked question is: Does artificialintelligence have the capacity to make moral decisions independently? Therefore, integratingmorality into AI algorithms is one of the priorities that interdisciplinary teamsfrom engineering and computer sciences, psychology, philosophy, sociology, law, etc.are intensively working on. This paper addresses this issue by presenting findings fromrelevant research which discusses the challenges and possibilities for integrating thedimensions of morality and introducing human values into autonomous systems thatperform complex tasks.
Keywords: morality; moral reasoning; moral decision making; artificial intelligence